Phage Therapy in Clinical Practice: Treatment of Human Infections - Kutter, Elizabeth; De Vos, Daniel; Gvasalia, Guram; Alavidze, Zemphira; Gogokhia, Lasha; Kuhl, Sarah; Abedon, Stephen T. (Current Pharmaceutical Biotechnology, 2010)
Phage therapy is the application of bacteria-specific viruses with the goal of reducing or eliminating pathogenic or nuisance bacteria. While phage therapy has become a broadly relevant technology, including veterinary, agricultural, and food microbiology applications, it is for the treatment or prevention of human infections that phage therapy first caught the world's imagination - see, especially, Arrowsmith by Sinclair Lewis (1925) - and which today is the primary motivator of the field. Nonetheless, though the first human phage therapy took place in the 1920s, by the 1940s the field, was in steep decline despite early promise. The causes were at least three-fold: insufficient understanding among researchers of basic phage biology; over exuberance, which led, along with ignorance, to carelessness; and the advent of antibiotics, an easier to handle as well as highly powerful category of antibacterials. The decline in phage therapy was neither uniform nor complete, especially in the former Soviet Republic of Georgia, where phage therapy traditions and practice continue to this day. In this review we strive toward three goals: 1. To provide an overview of the potential of phage therapy as a means of treating or preventing human diseases; 2. To explore the phage therapy state of the art as currently practiced by physicians in various pockets of phage therapy activity around the world, including in terms of potential commercialization; and 3. To avert a recapitulation of phage therapy's early decline by outlining good practices in phage therapy practice, experimentation, and, ultimately, commercialization.
Keywords: wound care